Diversity of Actinomycetes from Soil Samples Collected from Lombok Island, Indonesia - Lisdiyanti, Puspita; Tamura, Tomohiko; Ratnakomala, Shanti; Ridwan, Roni; Kartina, Gina; Lestari, Yulin; Ando, Katsuhiko; Widyastuti, Yantyati (BRIN, 2012)
A total of 137 strains of Actinomycetes were isolated from 14 soil samples collected in 3 part of Lombok Island, Indonesia using SDS-YE (SY) and Rehydration and Centrifugation (RC) isolation methods and Humic Acid Vitamin (HV) agar as isolation media. All the isolates were identified by morphological characteristic and by analysis of 16S rRNA gene sequence. On the basis of their morphology and 16S rRNA gene sequence, 67% of isolates were belonged to the Streptomyces Group and 33% of isolates were belonged to the Rare-Actinomycetes (Non-Streptomyces) Group. Nine families and 15 genera were found from the samples. It is indicated the richness of actinomycetes in these area. The genus Streptomyces is the most abundant in all soil samples, occupying 67% of all isolates by using SY method; while the genus Actinoplanes is mainly found by using RC as isolation method. Two strains belong to the genus Virgisporangium and Catenulispora that showed taxonomic interest need further study for describing as ne species.